Comparison between Average Linkage and K-Means Clustering Methods in Grouping Regencies or Cities by Open Unemployment Rate in Central Java - Sarah, Albertus Dion; Supriadin, Supriadin; Widiyanti, Karin Dita; Arsusma, Jesicha Roselina; Triky, Yolan; Arum, Prizka Rismawati (Jurnal Pendidikan Matematika, 2026)
Unemployment is a serious social and economic problem that hinders growth, including in Central Java Province. Based on the National Labor Force Survey (Sakernas), the unemployment rate in Central Java Province reached 5.96% in February 2021, an increase of 1.76% compared to February 2020. This study aims to compare two clustering methods, namely Average Linkage and K-Means Clustering, in grouping regions based on three indicators: population size, regencies/cities Minimum Wage (UMK), and labor force size. Evaluation was performed using the Silhouette Coefficient value to assess cluster quality. The analysis results indicated that the K-Means Clustering method with 2 clusters is the most optimal approach for classifying the open unemployment rate in Central Java Province. This is demonstrated by a higher Silhouette Coefficient value of 0.676 for K-Means Clustering, compared to 0.444 for the Average Linkage method. This clustering result divides the region into 2 clusters, namely the first cluster consisting of 8 regencies/cities and the second cluster comprising 27 regencies/cities. These findings are expected to assist local governments in formulating targeted unemployment mitigation policies. Pengangguran merupakan masalah sosial dan ekonomi serius yang menghambat pertumbuhan, termasuk di Provinsi Jawa Tengah. Berdasarkan Survei Angkatan Kerja Nasional (Sakernas), mencatat tingkat pengangguran di Provinsi Jawa Tengah mencapai 5.96% pada Februari 2021, atau meningkat 1,76% dibandingkan Februari 2020. Penelitian ini bertujuan membandingkan dua metode pengelompokan, yaitu Average Linkage dan K-Means Clustering, dalam mengelompokkan wilayah berdasarkan tiga indikator: jumlah penduduk, Upah Minimum Kabupaten/Kota (UMK), dan jumlah angkatan kerja. Evaluasi dilakukan menggunakan nilai Silhouette Coefficient untuk menilai kualitas cluster. Hasil analisis menunjukkan bahwa metode K-Means Clustering dengan jumlah 2 cluster merupakan pendekatan yang paling optimal dalam mengelompokkan tingkat pengangguran terbuka di Provinsi Jawa Tengah. Hal ini ditunjukkan oleh nilai Silhouette Coefficient yang lebih tinggi, yaitu 0.676 untuk K-Means Clustering, dibandingkan dengan 0.444 pada metode Average Linkage. Hasil klasterisasi ini membagi wilayah menjadi 2 cluster, yaitu cluster pertama yang terdiri dari 8 Kabupaten/Kota dan cluster kedua yang mencakup 27 Kabupaten/Kota. Temuan ini diharapkan dapat membantu pemerintah daerah dalam menyusun kebijakan penanggulangan pengangguran secara lebih tepat sasaran.